Revealing the inhibition mechanism of grain size gradient on crack growth in gradient nano-grained materials. (1st November 2019) - Li, Xiaotao; Zhao, Jianfeng; Zhang, Xu; Jiang, Xiaoyu
Abstract: Gradient nano-grained (GNG) materials, in which grain size changes from nano-scale in the surface to micro-scale in the core, have shown superior fatigue property, good strength and ductility. However, crack growth behaviors of GNG materials are studied hardly. In this work, the effect of grain size gradient on crack growth is investigated to reveal the inhibition mechanism of crack growth in GNG materials. The developed model employs a distributed dislocation method to model the evolution of plastic zone. The influence of grain size gradient on the distribution of dislocations in grains and the local stress intensity factor is analyzed. The results show that the sizes of dislocation zone and dislocation-free zone in grains become larger as the gradient of grain size increases. The number of dislocations emitted from the crack tip increases with the grain size gradient increasing, so the shielding effect of emitted dislocations on the crack growth increases and crack blunting becomes more serious. This means that a sharper grain size gradient inhibits the crack growth more effectively. The results in this paper are important for understanding the fracture behaviors of materials with grain size gradient and are helpful for material design and structural optimization.